2008
DOI: 10.1002/adfm.200701255
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Diffraction Efficiency of Photochromic Polymer Gratings Related to Photoinduced Dimensional Changes

Abstract: In this Full Paper, the possibility of reversibly changing the diffraction efficiency of gratings, fabricated by soft molding lithography on polymer films, containing photochromic molecules, is demonstrated. In particular, alternating UV and visible laser irradiation of the gratings causes the doped photochromic molecules to undergo transformations, which induce reversible dimensional changes to the samples. As a result, reversible changes are monitored in the intensity of the beams of a diode laser, transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The experimental results are confirmed by a theoretical diffraction model. It is proved that the diffraction efficiency changes are attributed exclusively to the reversible dimensional changes of the imprinted structures (Fragouli et al 2008), and not to the refractive index changes as is the case in the majority of previous works. Specifically, most of the gratings with similar thickness as the here presented, are produced after irradiation with interfering beams that cause variation of the refractive index inside the samples mainly consisting of azobenzene polymers and liquid crystals.…”
Section: Reversible Diffraction Efficiency Changes Of Photochromic Pomentioning
confidence: 84%
See 3 more Smart Citations
“…The experimental results are confirmed by a theoretical diffraction model. It is proved that the diffraction efficiency changes are attributed exclusively to the reversible dimensional changes of the imprinted structures (Fragouli et al 2008), and not to the refractive index changes as is the case in the majority of previous works. Specifically, most of the gratings with similar thickness as the here presented, are produced after irradiation with interfering beams that cause variation of the refractive index inside the samples mainly consisting of azobenzene polymers and liquid crystals.…”
Section: Reversible Diffraction Efficiency Changes Of Photochromic Pomentioning
confidence: 84%
“…(α is the period and β is the distance between the stripes, measured at the full width at half-maximum of each feature. (Fragouli et al 2008) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A proper choice of the polymer and PMs is necessary in order to tailor effectively the mechanical properties of the material, due to the usually quite low efficiency of the photomechanical effect. So far the photochromic blends of SP and polymers were proposed for applications in rather few papers, e.g., the works of Athanassiou et al 8,9 and Fragouli et al, 10 where it was shown that SP-polymeric films (5 to 10% wt.) can change reversibly their volume due to the isomeric transformations of the embedded photochromic molecules, acting as light-controlled mechanical actuators or as optical gratings with reversible diffraction efficiency.…”
mentioning
confidence: 99%